Development of clinical reasoning in an undergraduate medical program at a Brazilian university - Roberti, Alexandre; Roberti, Maria do Rosário Ferraz; Pereira, Edna Regina Silva; Porto, Celmo Celeno; Costa, Nilce Maria da Silva Campos (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: The cognitive processes relating to the development of clinical reasoning are only partially understood, which explains the difficulties in teaching this skill in medical courses. This study aimed to understand how clinical reasoning develops among undergraduate medical students. DESIGN AND SETTING: Quantitative and qualitative exploratory descriptive study conducted at the medical school of Universidade Federal de Goiás. METHODS: The focus group technique was used among 40 students who participated in five focus groups, with eight students from each year, from the first to fifth year of the medical school program. The material was subjected to content analysis in categories, and was subsequently quantified and subjected to descriptive statistical analysis and chi-square test for inferential statistics. RESULTS: The content of the students’ statements was divided into two categories: clinical reasoning — in the preclinical phase, clinical reasoning was based on knowledge of basic medical science and in the clinical phase, there was a change to pattern recognition; knowledge of basic medical science — 80.6% of the students recognized its use, but they stated that they only used it in difficult cases. CONCLUSION: In the preclinical phase, in a medical school with a traditional curriculum, clinical reasoning depends on the knowledge acquired from basic medical science, while in the clinical phase, it becomes based on pattern recognition.